STUDENT'S RECEPTION TOWARD SHAKESPEARE’S SELECTED CONTEMPORARY PLAYS - Dahlan; Junaid, Syahruni; Ahmad Muzammil; Rauf, Masykur (Elite : English and Literature Journal, 2022)
Literary reception is a literary genre that examines literary texts by considering the reader as the giver of the welcome or response. Researchers choose to analyze literary receptions in Shakespeare's plays, namely "Romeo and Juliet" and "Macbeth" as an interesting source of data to be studied and analyzed more deeply because of the difficulty of readers in responding to a literary work. This study aims to determine the reader's response to the two plays by Shakespeare. The data source of this research is the play script of "Romeo and Juliet" and "Macbeth" by William Shakespeare. The method used in this study is a qualitative descriptive method. This study uses Iser’s Reception theory with instruments in the form of documentation and observation studies because this research is reviewed by noting and marking the parts that are considered important and useful for the reader. Based on the results of this study, it is clear that there are reader responses in Shakespeare's plays. Then the results of the research are in the form of a questionnaire containing nine questions with excellent answers or responses from readers in engaging the two plays by Shakespeare.